Interlaboratory comparison of measuring results of magnetic field near 400 kV overhead power line - Grbić Maja; Pavlović Aleksandar (Zbornik Radova: Elektrotehnički Institut "Nikola Tesla", 2012)
The paper presents a comparison of measured results of magnetic field near 400 kV overhead power lines obtained by three laboratories. This interlaboratory comparison was performed to ensure confidence in the quality of the test results. The measured results were analyzed with standard methods, using En number, based on which the evaluation of the laboratories was performed.